Repellent activity of Cymbopogon citratus and Tagetes minuta and their specific volatiles against Megalurothrips sjostedti. (27th May 2019) - Diabate, Seydou; Martin, Thibaud; Murungi, Lucy Kananu; Fiaboe, Komi K. M.; Subramanian, Sevgan; Wesonga, John; Deletre, Emilie
Abstract: Cowpea is an important source of protein for people in Africa. However, the crop suffers major damage and yield losses due to bean flower thrips, Megalurothrips sjostedti Trybom (Thysanoptera: Thripidae). Although companion plants are known to reduce the damage caused by insect pests, the role of their volatiles in repelling pests from target plants has been the subject of few investigations. Here, we used the Y‐tube olfactometer experiments and chemical analyses to investigate the effect of volatiles from cowpea flowers and two companion plants; lemongrass, Cymbopogon citratus and Mexican marigold, Tagetes minuta on the olfactory responses of M. sjostedti . The results revealed that M. sjostedti males and females were repelled by the volatiles from freshly cut leaves of C. citratus . The combination of freshly cut leaves of C. citratus and cowpea flower was repellent to females but not to males. The female thrips, but not males, were repelled by the volatiles from the vegetative stage of T. minuta . Fifty‐four compounds were identified in the volatiles from two herbal plants. Among the major compounds, citral and a 4‐component blend comprised of dihydrotagetone, ( Z )‐3‐hexenyl acetate, limonene and ( Z )‐ β ‐ocimene repelled females but dihydrotagetone alone attracted females. While myrcene combined with cowpea flower volatiles enhanced the attraction of females M. sjostedti, when tested alone was not attractive. These results highlight the potential of volatiles from C. citratus and T. minuta to repel M. sjostedti females. The use of these plants as companion plants in a cowpea cropping system could reduce M. sjostedti infestation.